(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Nepal’s education system is undergoing significant transformations as it seeks to bridge the gap between traditional learning practices and modern pedagogical methods. This paper delves into the historical context of education in Nepal, exploring how ancient systems shaped the current landscape, while analyzing the reforms needed to integrate contemporary methods effectively. The objective is to highlight key challenges, examine ongoing reforms, and present a strategic framework to achieve a balanced, holistic approach to education in Nepal. The study emphasizes the role of cultural values, technology, and policy interventions in shaping the future of education in the country.